2001
DOI: 10.1177/070674370104601007
|View full text |Cite
|
Sign up to set email alerts
|

Separation Anxiety and Actual Separation Experiences during Childhood in Patients with Panic Disorder

Abstract: These results suggest that separation anxiety during childhood is not a consequence of actual traumatic separation experiences in panic disorder patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 38 publications
4
24
0
Order By: Relevance
“…Our data suggest that early parental loss and/or separation anxiety disorder affect the individual sensitivity to hypercapnic stimuli in a way that may remain stable through adulthood, regardless of the occurrence of panic attacks/disorder. Moreover, similarly to other studies [43], we found childhood parental loss and separation anxiety disorder only modestly correlated, suggesting that at least partially independent developmental pathways lead from parental loss and/or excessive worry about separation in childhood to PD in adulthood.…”
Section: Discussionsupporting
confidence: 89%
“…Our data suggest that early parental loss and/or separation anxiety disorder affect the individual sensitivity to hypercapnic stimuli in a way that may remain stable through adulthood, regardless of the occurrence of panic attacks/disorder. Moreover, similarly to other studies [43], we found childhood parental loss and separation anxiety disorder only modestly correlated, suggesting that at least partially independent developmental pathways lead from parental loss and/or excessive worry about separation in childhood to PD in adulthood.…”
Section: Discussionsupporting
confidence: 89%
“…The psychological literature on attachment (Dozier et al 1999) and several previous retrospective studies showed that SA might be associated with a broad range of adult psychiatric conditions (Gittelman & Klein 1984, Shear 1996, Bandelow et al 2001, Pini et al 2010, Miniati et al 2012.…”
Section: Consensus Ratings Based On Psychiatric Interviewmentioning
confidence: 99%
“…For example, while some investigators found that separation anxiety is significantly related to the development of panic disorder and agoraphobia (Bandelow et al, 2002;Laraia, Stuart, Frye, Lydiard, & Ballenger, 1994;Silove et al, 1995), others could not find confirmation for this hypothesis (Aschenbrand et al, 2003;Doerfler, Toscano, & Connor, 2008;Peter, Brückner, Hand, & Rufer, 2005;Thyer, Himle, & Fischer, 1988;Thyer, Nesse, Curtis, & Cameron, 1986). Moreover, the memory of separation anxiety in these studies was examined by self-report scales, which indicate that subjects were, in fact, aware of these events (Bandelow et al, 2001;Zitrin & Ross, 1988). However, according to psychoanalytic theory, it is the subject's unawareness of the specific childhood trauma, which is said to cause the development of fear and phobia (De Poderoso et al, 2005).…”
Section: Psychoanalysismentioning
confidence: 92%